Financial Ratio Analysis of Regional Revenue and Expenditure Budgets on Financial Performance in Regional Governments - Andi Sessu; Imaduddin (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2022)
This study aims to determine the regional financial performance of Makassar City in 2017-2019 seen from (1) Regional Financial Independence Ratio, (2) PAD Effectiveness Ratio, (3) Regional Financial Efficiency Ratio, (4) Growth Ratio, and (5) Ratio Shopping compatibility. This research is quantitative descriptive research conducted at the Regional Financial and Asset Management Agency of Makassar City. Data collection uses the documentation method. The results of the analysis show that the Regional Financial Performance of Makassar City as seen from (1) the Regional Financial Independence Ratio is still relatively low, indicating that the level of regional dependence on assistance from the central government is still very high because the average ratio is 7.15%. (2) Effectiveness Ratio based on APBD classified as Ineffective, with an average effectiveness of 83.05%. (3) Regional Financial Efficiency Ratio is classified as efficient because the average size of this ratio is 98.83%. (4) The Growth Ratio of PAD, Revenue, and Operational Expenditure always increases year after year, with fluctuating Capital Expenditure Growth. (5) The Expenditure Harmony Ratio can be said that the Makassar City Government allocates most of its budget for regional operating expenditure, namely an average of 78.23% compared to the average capital expenditure of 21.65%.